2013
DOI: 10.1080/13691058.2012.763187
|View full text |Cite
|
Sign up to set email alerts
|

‘We are despised in the hospitals’: sex workers' experiences of accessing health care in four African countries

Abstract: Sex workers in east and southern Africa are exposed to multiple occupational health and safety risks. Detailed understanding of barriers to accessing care would optimise design of improved services for this population. In this study, trained sex workers conducted in-depth interviews (n=55) and 12 focus group discussions with 106 female, 26 male and 4 transgender sex workers across 6 urban sites of Kenya, Zimbabwe, Uganda and South Africa. Data were analysed thematically, following an interpretive framework. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
238
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(258 citation statements)
references
References 18 publications
17
238
0
3
Order By: Relevance
“…The primary reason for choosing our questions from this earlier survey rather than the CCHS 2010 (which is much closer to the time when we developed the questionnaire for our sex workers study) is that the CCHS 2.1 includes "transportation problems" and "dislike doctors/afraid" as reasons for forgoing needed health care, whereas the CCHS 2010 survey excludes them; both lack of health services and fear of discrimination are highlighted in the sex work literature as potential major barriers to health care. [14][15][16][17] In an attempt to control for time variance in reasons for perceived health need, we compared relevant results from the 2003 and 2010 CCHS with regard to the reasons for unmet need, which were items present in both surveys (analysis available on request). While there was a slight increase in the prevalence of unmet health care needs between the earlier and later periods (14.9% vs. 17.2%), there were no significant differences in the proportion of the two main reasons for unmet need ("waiting time too long" and "not available when required") between the CCHS 2003 and 2010 surveys in the five CMAs.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The primary reason for choosing our questions from this earlier survey rather than the CCHS 2010 (which is much closer to the time when we developed the questionnaire for our sex workers study) is that the CCHS 2.1 includes "transportation problems" and "dislike doctors/afraid" as reasons for forgoing needed health care, whereas the CCHS 2010 survey excludes them; both lack of health services and fear of discrimination are highlighted in the sex work literature as potential major barriers to health care. [14][15][16][17] In an attempt to control for time variance in reasons for perceived health need, we compared relevant results from the 2003 and 2010 CCHS with regard to the reasons for unmet need, which were items present in both surveys (analysis available on request). While there was a slight increase in the prevalence of unmet health care needs between the earlier and later periods (14.9% vs. 17.2%), there were no significant differences in the proportion of the two main reasons for unmet need ("waiting time too long" and "not available when required") between the CCHS 2003 and 2010 surveys in the five CMAs.…”
Section: Datamentioning
confidence: 99%
“…Some studies have found that sex workers in Canada and elsewhere are reluctant to seek conventional health services, with reasons such as conflicts with other life commitments, not being aware of health clinics in their community, negative past experiences when seeking health care, embarrassment, fear of judgement, and discrimination. [14][15][16][17] Yet small participant numbers and homogenous samples weaken the generalizability of this body of work. Other studies focus only on those working for supervisors (e.g., for escort agencies or massage parlours) or on independent escorts typically delivering services in their own home or the client's locale.…”
mentioning
confidence: 99%
“…The perspective of this dissertation prioritizes a particularly "hard-to-reach population" receiving scant attention from outside Uganda (Bukenya et al 2013;Gysels et al 2002;Mbonye et al 2012;Mbonye et al 2013;Scorgie et al 2013;Sentumbwe 2010;Twinomugisha 2012;Zalwango et al 2010). Implicitly, dismissing this population as unimportant limits consideration towards understanding the interconnectivity of their HIV risks with the risks prevailing among Uganda's general population (Epstein 2007;Epstein and Morris 2011;Morris et al 1996).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…It was important that I use techniques that could accommodate rapid changes in the environment and with the individuals participating in the study. As I sought methods to best explore my subject, I soon realized most studies pursued information about women's daily risks with sex work, criminalization, and HIV/AIDS without considering women's experiences in connection to their larger social networks or without engaging in longer-term observation and participation in women's everyday practices (Bukenya et al 2013;Gysels et al 2002;Mbonye et al 2012;Mbonye et al 2013;Scorgie et al 2013;Sentumbwe 2010;Tamale 2009 andTwinomugisha 2012;Vandepitte et al 2011;Zalwango et al 2010). …”
Section: Aim Of the Studymentioning
confidence: 99%
See 1 more Smart Citation